PTU-097 Near hospital accommodation as an alternative to admission for patients undergoing complex endoscopy. (8th June 2018) - Goodchild, George; Odedra, Priyan; Potts, Jonathan R; Keane, Margaret G; Chapman, Michael H; Johnson, Gavin J; Pereira, Stephen P; Webster, George J
Abstract : Introduction: Use of hospital beds as pre/post procedure accommodation places a strain upon resources and risks 'on the day' cancellation. Nevertheless 'day case then home' may be a poor option for patients undergoing complex endoscopy who live many miles away. Our centre offers Near Hospital Accommodation (NHA) in a bespoke 35-roomed hotel 100 metres from the hospital at a cost of £120/night (versus £380 per inpatient bed). We aimed to assess the safety and utility of NHA for patients within our pancreatobiliary (PB) service. Methods: We undertook a retrospective audit of all PB patients who stayed in the NHA from Jan '15 – Dec '17. Data collected from the endoscopy database and electronic records included: procedure type, distance travelled, type of hotel room, length of stay and unplanned post-procedural hospital admissions from the NHA. Results: Over a 3 year period 152 patients stayed in NHA for 169 nights, ninety-three (61%) female with median age of 62 years (range 24–81). All patients underwent therapeutic ERCP, EUS, or cholangioscopy. The decision to use NHA was based upon case complexity and travel logistics. Most patients (89%) stayed one night and 11% stayed two nights (pre and post-procedure). Median one-way distance travelled was 107 miles (range 3–299 miles) (figure 1). The total cost of NHA was £23, 660, saving £40 560 over the equivalent inpatient beds. There were five unplanned admissions (3.3%), summarised in table 1. Conclusion: NHA is a safe, cost-effective alternative to hospital admission for selected patients undergoing complex endoscopy. The unplanned readmission rate was low, with no serious complications. The immediate cost saving was considerable, in addition to efficiency savings from the extra bed capacity generated and reduced late cancellations. Benefits to patients include visitor-friendly, hotel-standard accommodation, reduced travelling time on the day of the procedure and saving of private hotels fees. Further studies are needed to assess if this translates into increased patient satisfaction. With increasing centralisation of specialist services and ongoing financial pressures throughout the NHS, the NHA model of care offers advantages to hospitals and patients.